Identification and expression profile analysis of NUCLEAR FACTOR-Y families in Physcomitrella patens - Zhang, Fang; Han, Min; Lv, Qiang; Bao, Fang; He, YiKun (Frontiers in Plant Science, 2015)
NUCLEAR FACTOR Y transcription factors belong to a multimember family and consist of NF-YA/B/C subunits. Members of the NF-Y family have been reported to regulate physiological processes in plant. In this study, we identified and annotated two NF-YA, nine NF-B and twelve NF-YC proteins in the genome of Physcomitrella patens. Analyses of conserved domains demonstrated that PpNF-YA/B/C shared the same conserved domains with their orthologous proteins in Arabidopsis, O. sativa and mouse. Expression profiles indicated that PpNF-Ys were widely expressed in different tissues and developmental stages of P. patens throughout protonema and gametophores. The majority of PpNF-Y genes were responsive to abiotic stress via either ABA-independent or -dependent pathways. Some of ABA-regulated PpNF-Y expression were mediated by ABI3. To our knowledge, this study was the first to evaluate NF-Y families in Physcomitrella patens, and provides a foundation to dissect the function of PpNF-Ys.